2018
DOI: 10.1021/acsenergylett.8b01114
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Boosting Li-Ion Current in Silicon Nanoparticles

Abstract: Improvement in the rate capability needs to be addressed for utilization of a Si anode in high-power Li-ion batteries. Regarding the rate capability, its improvement by Si–C nanocomposites seems to be somewhat saturated, thus indicating that the other method should be tried for further enhancement of the rate capability. Here, we introduce Si nanoparticles uniformly coated with nanometer-thick polyacrylonitrile (PAN) with better wettability to liquid electrolytes and minimizing electronic resistance, which mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…To further elucidate the performance differences between p‐SiNSs and p‐SiNSs@C‐2 electrode, the contact angles were examined. As shown in Figure a,b, the contact angles of p‐SiNSs and p‐SiNSs@C‐2 electrodes are 21.9 and 8.6, which shows the p‐SiNSs@C‐2 electrode has better wetting of the electrolyte than p‐SiNSs . The morphology and thickness diversification are direct evidences to certificate the electrochemical performances of batteries.…”
Section: Resultsmentioning
confidence: 86%
“…To further elucidate the performance differences between p‐SiNSs and p‐SiNSs@C‐2 electrode, the contact angles were examined. As shown in Figure a,b, the contact angles of p‐SiNSs and p‐SiNSs@C‐2 electrodes are 21.9 and 8.6, which shows the p‐SiNSs@C‐2 electrode has better wetting of the electrolyte than p‐SiNSs . The morphology and thickness diversification are direct evidences to certificate the electrochemical performances of batteries.…”
Section: Resultsmentioning
confidence: 86%
“…Peaks shown using X-ray photoelectron spectroscopy (XPS) could be attributed to carbon and silicon ( Figure 2D); the Si peaks are much lower than the peak of carbon because the silicon is completely wrapped by the graphene scroll. In the case of the high-resolution XPS spectra, C 1s (Figure 2E), peaks fitted at ∼284.1, ∼285.4, and ∼286.2 eV are successively assigned to graphene surface functional groups of C-C, C = C, and C-O, respectively (Song et al, 2018). For the XPS spectrum, Si 2p could be derived from two peaks located at 99.5 and 104 eV ( Figure 2F), which could be attributed to Si and SiO 2 , respectively (He et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figures 5C,D, the Si@rGONSs-2 electrode after 100 cycles retains its original appearance with no crack or peel-off phenomenon (Xu et al, 2018). The contact angles of commercial Si and Si@rGONSs-2 electrode are 20.2 and 9.5 • , respectively (Figures S6A,B), which shows that the Si@rGONSs-2 electrode has better electrolyte wetting performance compared with commercial Si (Song et al, 2018). Better electrolyte wetting and the open tubular structure provides space to handle variation in volume; thus, the Si@rGONSs-2 electrode possesses outstanding stability and reversibility.…”
Section: Figure 4 | (A)mentioning
confidence: 86%
“…reported that their rate capability test on Si nanoparticles is up to 8C (8 A g −1 ) for 300 cycles [27] . Several rate capability tests have been reported on a silicon‐based half‐cells, but the tests were limited up to 150 cycles without considering extended cycling [28–32] …”
Section: Introductionmentioning
confidence: 99%